Future expansion and prospects of Turkish defense industry - János Besenyő; András Málnássy (Insights into Regional Development)
The global military industry, like the Turkish military industry, has undergone and is undergoing a major transformation in the 21st century. The faster and faster coming-out of new technologies and economic ecosystems are transforming the military industry as well while the latter used to make slow responses and changes otherwise. New players and companies are emerging and expected to become increasingly important. In this changing environment, the Turkish military industry needs to produce tools and systems that meet the requirements of them: to be technologically of high quality, to be competitive in terms of prices, and to have security of supply in the event of a crisis. A changing global field and security environment, where the interdependence of national economies is increasing, make increasingly difficult to meet these three expectations simultaneously.